The Contemporary Chinese Media System and Its Influence in the Global Information Space: The Case of CGTN, Xinhua, and Weibo (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study explores the structure, function, and global communicative influence of China’s contemporary media system through an in-depth analysis of three major platforms: CGTN, Xinhua News Agency, and Weibo. Positioned at the intersection of political control and digital modernization, these platforms represent China’s strategic efforts to shape global narratives, project soft power, and reinforce its geopolitical identity. Utilizing a qualitative content analysis grounded in media-system theory and discourse studies, the research examines how these platforms frame China’s role in international diplomacy, development, and public opinion management. The study also compares Chinese media strategies with those of Uzbekistan’s online outlets (Gazeta.uz, Kun.uz), revealing stark differences in narrative construction, audience engagement, and global outreach. The findings demonstrate that while Chinese media are highly centralized and message-consistent, they integrate sophisticated technological tools and multilingual strategies to broaden their global reach. In contrast, Uzbek media maintain a more domestically oriented and interactive approach, with less alignment to state-driven narratives. The study concludes that the Chinese media system serves not only as a tool of internal control but also as a dynamic model of external influence, increasingly shaping global discourse in the digital age.